Estudantes com autismo e a preparação para o mundo do trabalho: um estudo sobre a educação profissional de nível médio no IFBA - Ferreira, Vânia da Silva (Universidade Federal de São Carlos, 2023)
The present study aimed to investigate how the professional training of students with ASD at a Federal Institute of Bahia has been consolidating, using information obtained from the students themselves, as well as from their teachers, support professionals and family members. The specific objectives of the study were: i) to analyze the perspectives of teachers, support professionals, students and family members regarding the insertion of students with ASD in the common spaces of regular teaching of secondary professional education and ii) to investigate the conditions offered in this training for the inclusion and permanence of students with ASD. The study was carried out on one of the twenty-two campuses of the Federal Institute of Bahia and involved 18 participants, 03 students with ASD, 10 teachers who teach classes for these students, 02 school support professionals and 03 family members, this study guided by an exploratory descriptive method. The study took place in the following stages: data collection, which took place through a script of semi-structured interviews with all participants, with questions prepared according to four categories: 1) School inclusion; 2) Pedagogical practices adopted by teachers; 3) Prospects for the future of students and their families regarding professional training; 4) Relationships between peers (execution of group activities and friendship bonds) carried out through Google Meet and in the study on formative and acting experiences in the service of students with ASD. Data analysis was based on the technique of content analysis using the Atlas.Ti software in the organization and categorization of data and with the theoretical support of the literature on special education and ASD. The survey results revealed important information about the positive aspects and points to be improved in the experiences of students with ASD in high school professional education. The crucial importance of the teaching staff and support professionals in the school inclusion of these students was highlighted. Adequate training, which includes the implementation of a functional curriculum and the strengthening of the relationship between teacher and student, proved to be essential to facilitate the teaching and learning process. In addition, families play an essential role in the academic trajectory, fighting for the rights and access to education for their children with ASD. It is necessary to provide more assertive guidance to students with ASD regarding their professional choice, as the results indicated difficulties in understanding this process and future prospects after completing the course.
Students with autism and preparation for the world of work: a study on mid-level professional education at the IFBA
Keywords: Educação Especial; Transtorno do espectro do autismo; Ensino técnico e profissional; Special education; Autism spectrum disorder; Professional education; CIENCIAS HUMANAS::EDUCACAO